Pet CBD market in the Czech Republic - Bambasová, Klára; Ryška, Tomáš, 1976-; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
The focus of this thesis is on CBD (cannabidiol), a substance extracted from cannabis, and its perception amongst Czech society. The subject is first viewed from the global dimension, after which the focus concentrates on the local dimension and the point of view of the Czech citizen and/or potential consumer. The perception of CBD is being examined through research performed for the ultimate purpose of finishing the thesis. Further attention is being paid to the social aspects as well as to the legal aspects, concerning the usage and sales of CBD products. All of the previously mentioned steps build up a path to the goal: to be able to suggest the ideal marketing communication for Releaf s.r.o.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses